2009
DOI: 10.2174/092986709788682191
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Human Serum α1-Acid Glycoprotein and Albumin Binding of Various Marketed and Preclinical Kinase Inhibitors

Abstract: There are about 380 protein kinase inhibitors in drug development as of today and 15 drugs have been marketed already for the treatment of cancer. This time 139 validated kinase targets are in the focus of drug research of pharmaceutical companies and big efforts are made for the development of new, druglike kinase inhibitors. Plasma protein binding is an important factor of the ADME profiling of a drug compound. Human serum albumin (HSA) and alpha(1)-acid glycoprotein (AAG) are the most relevant drug carriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 77 publications
0
47
1
Order By: Relevance
“…By using the induced circular dichroism (ICD) spectroscopy, Zsila et al previously reported AAG and albumin values of sorafenib Kd which are approximately 2-and 100-fold higher than ours, respectively (13). Differing experimental conditions may account for the large discrepancy in albumin values of sorafenib Kd between the two investigations.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…By using the induced circular dichroism (ICD) spectroscopy, Zsila et al previously reported AAG and albumin values of sorafenib Kd which are approximately 2-and 100-fold higher than ours, respectively (13). Differing experimental conditions may account for the large discrepancy in albumin values of sorafenib Kd between the two investigations.…”
Section: Discussioncontrasting
confidence: 51%
“…In this context, characterizing the sorafenib binding to albumin is of critical pharmacological and clinical interest. Finally, Zsila et al recently showed that sorafenib also binds to α1-acid glycoprotein (AAG) (13), although this result is in disagreement with the data provided by the manufacturer of sorafenib (11). As serum AAG concentration can be increased by 1.6-3.0 fold in several neoplasia, AAG may potentially be a parameter influencing sorafenib CL.…”
mentioning
confidence: 91%
“…The level of AAG is increased in neoplasms, while HSA is markedly depressed in progressive malignancies [187].…”
Section: Plasma Protein Bindingmentioning
confidence: 97%
“…HSA binding has been intensively investigated [41,186,187]. HSA is a singlechain protein that contains several binding sites for drugs, including site I and site II (indole-benzodiazepine site) (Figures 2.16 and 2.17).…”
Section: Plasma Protein Bindingmentioning
confidence: 99%
See 1 more Smart Citation